Menulis Kalimat Argumentatif : Kemampuan dan Tantangan Peserta Didik Kelas IV Sekolah Dasar - Ana Istiqomah Asyraf; Chandra Chandra; Inggria Kharisma (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This study aims to analyze the abilities and challenges of grade IV elementary school students in writing argumentative sentences. The research was conducted with a qualitative approach of case study methods on ten students in one of the public elementary schools in Jambi City. Data were obtained through an argumentative sentence writing test and analyzed using the Miles and Huberman model which includes data reduction, data presentation, and verification. The results of the study show that students' ability to write argumentative sentences still varies. Most of the students have been able to convey their opinions in a concise and relevant manner, but there are still obstacles in the mechanical aspects of writing such as the use of spelling, punctuation, and sentence structure. These findings show the need for a learning strategy that can develop argumentative writing skills systematically and logically. Toulmin's pattern-based approach and collaborative learning models such as Group Investigation are recommended to improve students' overall argumentative writing skills from the elementary school level.